125k views
5 votes
Find the sum and express it in the simplest form (-2y-4x+7)+(-4y+x-1)

2 Answers

2 votes

Answer:

-6y - 3x + 6

Explanation:

All you are doing is combining like-terms the whole way.

I am joyous to assist you anytime.

User Hatem Alimam
by
5.3k points
3 votes

Y=7+2x......(1)

put this value in 4y+x=1

4(7+2x)+x=1

28+14x+x=1

15x=-27

x=-27/15.....(2)

put this value in eqn (1)

y=7+2(-27/5)

y=7-54/5

y=-3.8

I really hope this helps :D:D:D!!!!

User Abdullah Al Imran
by
4.8k points